Organisasi Peradilan Tata Usaha Negara Dalam Peradilan di Indonesia - Malaka, Zuman; Isa, Abdullah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The judiciary is the executor of judicial power in charge of administering the judiciary in order to enforce law and justice based on Pancasila, with other tasks assigned to it based on the applicable law. In the framework of the rule of law, the existence of a state administrative court is essentially a logical consequence of the principle of government based on law (wetmatigheid van het bestuur). For the Indonesian people, the existence of this state administrative court is a court that is considered young, and contains provisions and procedural concepts that are universal. In state administrative law courts, of course, the principles of state administrative court procedures are needed which include the principle of activity, the principle of not knowing conversion, the principle of not knowing peace, the principle of presumtea iustaecausa, the principle of protection of the public interest.